Relationship between swimming performance and shoulder muscle strength in elite Chinese water polo players - Ren, S.; Li, W.; Zhang, Z.; Cao, F. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background The relationship between swimming performance and shoulder muscle strength at different swimming distances is unclear. To provide a theoretical basis for future targeted training as well as better detection and prevention of water polo related injuries.